THE ROLE OF METHODICAL EDUCATION IN MILITARY EDUCATIONAL INSTITUTIONS - Musalim Nuriddinov (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation. Achieving high results in studies and subsequent service by cadets of military educational institutions in completing assigned tasks is directly related to their personal characteristics, including the presence of leadership qualities.